2021
DOI: 10.1080/19336918.2021.1921402
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ENST00000508435 promotes migration of breast cancer via FXR 1

Abstract: LncRNA plays a critical role in tumor progression. However, the role it executes in breast cancer is still unclear. Here, we report a newly discovered lncRNA, ENST00000508435 , which could be remarkably up-regulated in breast cancer cells and tissues. We found that the expression of ENST00000508435 was positively correlated with tumor size, lymph node metastasis and HER2. More interesting, overexpression of ENST00000508435 significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A more recent study indicated that there was a direct association between FXR1 expression and cell abilities to survive and proliferate in cancers [22]. In addition, FXR1 was demonstrated to negatively relate with the prognosis, and was highly expressed in human cancers including prostate cancers, breast cancers [17,23]. In this article, FXR1 overexpression was observed in ccRCC cells.…”
Section: Discussionmentioning
confidence: 62%
“…A more recent study indicated that there was a direct association between FXR1 expression and cell abilities to survive and proliferate in cancers [22]. In addition, FXR1 was demonstrated to negatively relate with the prognosis, and was highly expressed in human cancers including prostate cancers, breast cancers [17,23]. In this article, FXR1 overexpression was observed in ccRCC cells.…”
Section: Discussionmentioning
confidence: 62%